3D interactive animation learning for dyslexic children / Nor Bibi Maslina Jusoh - Nor Bibi Maslina , Jusoh (2018)
Dyslexia children are known as having difficulties to learn letters and numbers due to their brain inability to interpret objects into letters and words. Their abnormal interpretation of letters and words compared to normal children abstained themselves from long words and sentences. This inability caused problems in mastering reading and writing skills. To date, numerous studies have focused on developing or inventing learning aids in the format of real is or authentic materials for dyslexia children. Studies also have documented the remarkable progress of dyslexia children of whom turned out to be Information Communication Technology (ICT) literate when they grew up. This development signifies the ability of ICT in unburying and molding the talent of dyslexia children. Today’s development in multimedia software and hardware is a new hope for these children in mastering literacy skills. However, despite the research and technological innovation outcomes, effort to benefit their ICT inclination by integrating their learning with ICT elements is still sparse. This study attempts to aid the learning process of dyslexia children via 3D tool, named ThreeDLexic. Focusing on specific 3D alphabets which was identified from a 3-month pilot project held at the research center for PDM (Persatuan Dyslexia Malaysia), a 3-month observation was conducted on 174 participants to obtain the data. Once the application is ready, a three month observations will also be conducted at the same center. 3D and dyslexia children are inter-related. So it is very hopeful that the application of 3D will be highly beneficial in the learning process of children with dyslexia.